The Role of the Principal as a Supervisor on Teacher Performance at SMP Negeri 6 Tanimbar Utara - Delce Kainama; Fricean Tutuarima; Aisa Abas (Journal of Education Technology Information Social Sciences and Health, 2024)
Professional teachers will carry out their duties properly and correctly to produce higher quality graduates. This is supported by the role of the school principal as a supervisor who has the task of improving teacher performance in an effort to realize a better learning process through more efficient teaching methods, the ability to master a wide range of material which makes it possible to guide students to meet competency standards. This research aims to describe the role of the principal as a supervisor in improving teacher performance. A teacher has an important role in forming the knowledge, skills and character of students. This research is a qualitative descriptive study using a special study approach. By observing the role of the principal as a supervisor in improving teacher performance at SMP Negeri 6 Tanimbar Utara. The subjects of this research were the principal and 7 teachers. The object of this research was the role of the principal as a supervisor in improving teacher performance at SMP Negeri 6 Tanimbar Utara. This research uses data collection techniques by means of observation, interviews and documentation. Primary data was selected directly from respondents, while secondary data consisted of theories from books and journals and other support obtained from school documentation. Meanwhile, data validity testing was carried out by source triangulation. Data analysis 95in this study used data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that the role of the principal as supervisor in improving teacher performance at SMP Negeri 6 North Tanimbar has not carried out his role properly and correctly as a supervisor.  This is indicated by the decline in teacher awareness in developing performance and in-depth mastery of the material, as well as increasing teacher indiscipline in carrying out their duties and responsibilities